2018
DOI: 10.1016/j.jid.2017.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Topical Reformulation of Valsartan for Treatment of Chronic Diabetic Wounds

Abstract: Chronic wounds are among the most devastating and difficult to treat consequences of diabetes. Dysregulation of the skin renin-angiotensin system is implicated in abnormal wound healing in diabetic and older adults. Given this, we sought to determine the effects of topical reformulations of the angiotensin type 1 receptor blockers losartan and valsartan and the angiotensin-converting enzyme inhibitor captopril on wound healing in diabetic and aged mice with further validation in older diabetic pigs. The applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
47
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 46 publications
1
47
2
Order By: Relevance
“…Although the losartan group had the similar results at the final day, as we wanted to focus on the effect of ACEI, the further studies were not involved. Interestingly, recent study reported that applying valsartan (one of angiotensin receptor blockers) topically was a favourable treatment for chronic diabetic wounds (Abadir et al, ). Future studies should elucidate the effects of angiotensin receptor blockers on scar formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the losartan group had the similar results at the final day, as we wanted to focus on the effect of ACEI, the further studies were not involved. Interestingly, recent study reported that applying valsartan (one of angiotensin receptor blockers) topically was a favourable treatment for chronic diabetic wounds (Abadir et al, ). Future studies should elucidate the effects of angiotensin receptor blockers on scar formation.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who are already on an ACEI for hypertension or other cardiovascular conditions would be benefit from it, and this would have been a good indication for ACEIs. Since wound healing could be better achieved in both mice and pigs by giving valsartan topically (Abadir et al, ), we also should explore the topical application for scar management, like transdermal administration. Further, a comparison between systemic and topical administration of ACEI will be needed in addition to further experiments in order to clarify if ACEI may also represent a novel therapeutic approach to other dermatological disorders in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, innovative therapies are needed. Recently, the role of the renin–angiotensin system (RAS) in wound healing has been characterized in animal models . Given the availability and excellent safety profile of various RAS modulators, successful repurposing of these drugs to improve healing of chronic ulcers may prove useful in clinical settings.…”
mentioning
confidence: 99%
“…Given the availability and excellent safety profile of various RAS modulators, successful repurposing of these drugs to improve healing of chronic ulcers may prove useful in clinical settings. Considering recent reports supporting a mechanism of action for RAS modulation for the improvement of healing, we hypothesized that topical delivery of a RAS modulator would improve wound healing. Herein we report our experience of treating VLUs with a topical formulation of valsartan 1% ointment.…”
mentioning
confidence: 99%
See 1 more Smart Citation